Analgesia in clinically relevant rodent models of sepsis. (December 2016) - Jeger, Victor; Hauffe, Till; Nicholls-Vuille, Flora; Bettex, Dominique; Rudiger, Alain
Postoperative analgesia in rodent sepsis models has been considerably neglected in the past. However, intentions to model clinical practice, increasing awareness of animal ethics, efforts to apply the 3Rs (replacement, reduction, refinement), and stricter legislation argue for a change in this respect. In this review, we describe different concepts of analgesia in rodent models of sepsis focusing on opioid agonists as well as non-opioid analgesics. Advantages and pitfalls in study design and side-effects are discussed. Score sheets should be used to adapt analgesia or to terminate experiments using humane endpoints. Further research is needed to differentiate behavioral changes caused by sepsis and pain or as a consequence of analgesia. Information on the efficacy of analgesia in sepsis models is scarce. Hence, studies are needed to identify the best ways to reduce suffering of research animals and thereby optimize the clinically relevant rodent models of sepsis.